Digital sleep measures and white matter health in the Framingham Heart Study - Robert Joseph Thomas; Hyun Kim; Pauline Maillard; Charles S. DeCarli; Eric James Heckman; Cody Karjadi; Ting Fang Alvin Ang; Rhoda Au (Open Exploration Publishing Inc., 2021)
Aim:Impaired sleep quality and sleep oxygenation are common sleep pathologies. This study assessed the impact of these abnormalities on white matter (WM) integrity in an epidemiological cohort. Methods:The target population was the Framingham Heart Study Generation-2/Omni-1 Cohorts. Magnetic resonance imaging (diffusion tensor imaging) was used to assess WM integrity. Wearable digital devices were used to assess sleep quality: the (M1-SleepImageTM system) and the Nonin WristOx for nocturnal oxygenation. The M1 device collects trunk actigraphy and the electrocardiogram (ECG); sleep stability indices were computed using cardiopulmonary coupling using the ECG. Two nights of recording were averaged. Results:Stable sleep was positively associated with WM health. Actigraphic periods of wake during the sleep period were associated with increased mean diffusivity. One marker of sleep fragmentation which covaries with respiratory chemoreflex activation was associated with reduced fractional anisotropy and increased mean diffusivity. Both oxygen desaturation index and oxygen saturation time under 90% were associated with pathological directions of diffusion tensor imaging signals. Gender differences were noted across most variables, with female sex showing the larger and significant impact. Conclusions:Sleep quality assessed by a novel digital analysis and sleep hypoxia was associated with WM injury, especially in women.